LINGUISTIC BASIS OF LEARNING POLYSEMANTIC WORDS AT SCHOOL - Ibragimova Saodat Mukhsinovna (Western European Studies, 2023)
In this article, the Russian language program focuses on vocabulary enrichment, particularly in the area of polysemy of words. Traditionally, this has been achieved through the quantitative accumulation of new words. However, due to increased demands on students' speech culture, it is now necessary to focus on qualitative enrichment, focusing on revealing and mastering the polysemy of already known words.
Keywords: phonemes; process of communication; unit of language